Ultrasound examination of pneumonia-infected lungs - Elena V. Chuyashenko; Vera D. Zavadovskaya; Tatyana S. Ageeva; Nataliya M. Prosekina; Tatyana B. Perova (Бюллетень сибирской медицины, 2017)
In the last few decades the content of diagnostic information provided by ultrasound examination of the chest in a wide spectrum of diseases (pneumonia, peripheral tumors, pleural diseases, pneumothorax) has been widely discussed. The advantages of ultrasound examination (the lack of radiation exposure, image in real time, the distinct visualization of pulmonary subpleural portions and costal diaphragmatic sinuses) provide the possibility to use ultrasound in pediatric practice for frequent monitoring of pneumonia dynamics. The use of ultrasound examination in the diagnostic algorithm in adult patients with pneumonia is not widely used in Russian clinical practice.The article gives the details about the technique of ultrasound examination of the chest, ultrasound anatomy, the impact of the morphological substrate of the pathological formation on the ultrasound picture, and its localization and length. The review of bibliography data about ultrasound semiotics of pneumonia depending on the type of inflammatory infiltrate (hypo and hyperechoic structure of various shapes, length, artifacts, A-line, -line). The necessity of ultrasound use for monitoring pneumonia in order to assess the therapy efficacy has been proven (this is a very strong statement, I would say it “has been supported”.It is indicated that the possibility of ultrasound examination depending on morphological forms of inflammation has not been disclosed and there are no data about the comparison of ultrasound, X-ray and computed tomography. The recommended frequency of the ultrasound monitoring of different inflammatory lung diseases has not yet been determined (this makes it sound like there are no results).This article indicates that ultrasound examination can take its important place as an option in the diagnosis in patients with inflammatory lung diseases due to the safety and wide availability of this method in combination with the CDK.